2021
DOI: 10.1002/pls2.10034
|View full text |Cite
|
Sign up to set email alerts
|

Waste plastics in asphalt concrete: A review

Abstract: Among possible applications for post-consumer waste plastics, one criterion is that the application should be able to use very large amounts of material because the amount of plastic waste is so large. Another key issue is economics; very little cost should be involved in preparing waste plastics for a specific application. One of the few applications for post-consumer waste plastics that could possibly meet both requirements is filler in asphalt concrete. Specifically, if waste plastics in asphalt concrete we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 107 publications
(110 reference statements)
0
23
0
1
Order By: Relevance
“…The clear asymmetric (002)-band, which is also known as Π-band or graphene-band, settled at 2θ = 23.92 • originates from the stacks of condensed aromatic sheets [68]. The twodimensional lattice (10) and (11) reflections, or (100) and (110) reflections emerge eventually from the in-plane structure of aromatics. They belong to the first and second neighbors in the ring components.…”
Section: X-ray Diffraction Spectroscopy (Xrd)mentioning
confidence: 99%
See 1 more Smart Citation
“…The clear asymmetric (002)-band, which is also known as Π-band or graphene-band, settled at 2θ = 23.92 • originates from the stacks of condensed aromatic sheets [68]. The twodimensional lattice (10) and (11) reflections, or (100) and (110) reflections emerge eventually from the in-plane structure of aromatics. They belong to the first and second neighbors in the ring components.…”
Section: X-ray Diffraction Spectroscopy (Xrd)mentioning
confidence: 99%
“…Various forms of recycled materials and/or by-products have demonstrated a great potential to serve as a promising ingredient for road pavement construction such as reclaimed asphalt pavement (RAP) [3], construction and demolition waste (C&D waste) [4], waste rocks [5], cement dust [6], waste glass [7], wood sawdust [8], rice husk and straw [9,10], plastic waste [11], crumb rubber [12], waste cooking oil and waste engine oil [13], and others. Certainly, the use of reclaimed materials may offer short-and long-term social, economic, and environmental advantages ranging between conserving natural resources and landfill space, curbing greenhouse gas emissions, minimizing energy consumption, lowering highway maintenance costs, and of course building sustainable pavements [14].…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been reported that recycled plastics can be used as modifiers or aggregate substitute in the construction of flexible pavements, thereby resulting in a reduction in their expenses [14]. The incorporation of waste plastic at small doses (ranging between 5% and 10% by weight of binder) into bituminous road construction can improve pavement stability, strength, and durability substantially [15]. Laboratory tests have shown that employing shredded waste plastic in asphalt mixtures results in higher resistance to permanent deformation (i.e., flow rutting) and greater moisture damage resistance, thereby leading to accident reduction [16].…”
Section: Introductionmentioning
confidence: 99%
“…Based on data from the USEPA (U.S. Environmental Protection Agency), 29.2% of the total plastics in the municipal solid waste stream is PE. Existing studies have shown that modification of asphalt mixtures with plastics leads to increased rut resistance and lower moisture damage ( 10 ). Studies on the effects of plastic modification on low-temperature cracking and fatigue cracking are limited at this point ( 11 ).…”
mentioning
confidence: 99%
“…More broadly, research on the use of PCR plastics in asphalt has received significant global attention in recent years, driven in part by China’s recent shift away from PCR plastic imports starting in 2018. Even before 2018, research on the incorporation of PCR plastics into asphalt mixtures was underway in countries other than the U.S., such as India, China, Australia, UK, and Malaysia ( 9 , 10 ). An immensely wide variety of plastics with differing chemical composition exist in the recycling marketplace.…”
mentioning
confidence: 99%